2020
DOI: 10.1016/j.jvscit.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic arteriovenous malformation of the superficial temporal artery

Abstract: An arteriovenous malformation is a rare vascular anomaly composed of a complex network of interconnected arteries and veins of the scalp. It is usually congenital, but infrequently occurs after trauma. Over the years, several terms have been used to describe these lesions, such as cirsoid/rasemose/arteriovenous aneurysm, plexiform angioma and aneurysma serpentinum, or arteriovenous fistula when a single connection exists. Head and neck malformations occur in 0.1% of the population. Involvement of the superfici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…However, the disruption theory suggests that the vasa vasorum during trauma ruptures and activates a cellular reaction within endothelial cells and thus creating vascular connections between arteries and veins. The iatrogenic cases were thought to arise at sites of previous interventions such as hair transplantations and craniotomies [ 1 , [4] , [5] , [6] ]. Among the six patients included in our study, none have reported a history of trauma and most likely their presentation is explained by one of the congenital hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the disruption theory suggests that the vasa vasorum during trauma ruptures and activates a cellular reaction within endothelial cells and thus creating vascular connections between arteries and veins. The iatrogenic cases were thought to arise at sites of previous interventions such as hair transplantations and craniotomies [ 1 , [4] , [5] , [6] ]. Among the six patients included in our study, none have reported a history of trauma and most likely their presentation is explained by one of the congenital hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms were progressive swellings, headache, local pain, audible bruits, tinnitus, and cosmetic concerns [ [1] , [2] , [3] , [5] , [6] , [7] ]. All patients included in our study reported swelling and only one patient out of six had associated headache and dizziness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 20% of arteriovenous malformations involving the scalp are associated with a history of trauma [ 93 ]. Arteriovenous malformations of the head and neck occur in 0.1% of the population and TA is involved in 75% of scalp arteriovenous malformations [ 94 ]. Clinically, the patient may present with headache, local pain, paresthesias, tinnitus, ischemic necrosis, or nidus ulceration and hemorrhage associated with thrill on palpation [ 94 ].…”
Section: Others Temporal Artery Vascular Diseasesmentioning
confidence: 99%
“…Las malformaciones arteriovenosas extracraneales de cabeza y cuello son raras y difíciles de manejar. Varias opciones de tratamiento se han descrito para tratar estas lesiones [1]. A continuación, presentamos una serie de dos casos de malformaciones arteriovenosas extracreaneales que se trataron exitosamente con resección quirúrgica.…”
Section: Introduccionunclassified